Association of serum BDNF levels with psychotic symptom in chronic patients with treatment-resistant depression in a Chinese Han population. (November 2017) - Huang, Xingbing; Huang, Xiong; Zhou, Yanling; He, Hongbo; Mei, Fang; Sun, Bin; Soares, Jair C.; Yang Zhang, Xiang
Abstract: The neurotrophic hypothesis of depression is supported by consistent findings of lower serum BDNF levels in depressed patients. Increasing evidence shows different clinical characteristics of patients with psychotic major depression versus nonpsychotic major depression. However, the possible association between BDNF and psychotic symptoms in depression has not been investigated. We recruited 90 treatment-resistant depression (TRD) patients and 90 gender- and age-matched healthy control subjects and examined serum BDNF in both groups. Patients' depressive symptoms were assessed using the 17-item Hamilton Depression Rating Scale (HDRS-17), and psychopathological symptoms by the 18-item Brief Psychiatric Rating Scale (BPRS-18). Our results showed that BDNF levels were significantly lower in patients than controls. Correlation analysis revealed a significantly positive correlation between BDNF and the thought disturbance subscale of BPRS-18 (p < 0.05), and a trend toward a significantly positive correlation between BDNF and the BPRS-18 total score (p = 0.06). Stepwise multiple regression analyses confirmed BDNF as the influencing factor for the thought disturbance subscales of the BPRS-18. Our findings suggest that BDNF may be involved in the pathophysiology of TRD, and its associated psychotic symptoms, especially thought disturbance. Highlights: Serum BDNF was measured in 90 treatment-resistant depression patients and 90 controls. Patients were rated on depression and psychopathological symptoms. BDNF levels were significantly lower in patients than controls. A positive correlation was noted between BDNF and thought disturbance symptom in patients.